Adipocytes and intestinal epithelium dysfunctions linking obesity to inflammation induced by high glycemic index pellet-diet in Wistar rats. Issue 3 (27th June 2018) - Luz, Anna Beatriz Santana; dos Santos Figueredo, Júlia Braga; Salviano, Bianca Damásio Pereira Dantas; Aguiar, Ana Júlia Felipe Camelo; Pinheiro, Luiza Gabriella Soares Dantas; Krause, Matheus Felipe Dantas; da Silva Camillo, Christina; Ladd, Fernando Vagner Lobo; Bortolin, Raul Hernandes; Silbiger, Vivian Nogueira; Maciel, Bruna Leal Lima; de Araújo Morais, Ana Heloneida
Abstract : We investigated the inflammatory effect of a pellet-diet with high glycemic index and load (HGLI) on the histological organization of adipocytes, intestinal epithelium, and fat in liver and pancreas in adult male Wistar rats. Two groups ( n =10) received for 17 weeks: (1) HGLI diet or (2) Standard diet (Labina®). Histological analyses of adipose tissue, jejunum, liver, and pancreas were performed. Stereology analysis, visceral adiposity index, gene expression, and immunohistochemistry of tumor necrosis factor-α (TNF-α) in visceral adipose tissue and plasma TNF-α were also assessed. The HGLI diet-induced hypertrophy of adipocytes with adipocyte volume density equal to 97.0%, cross-sectional area of adipocytes equivalent to 1387 µm² and a total volume of adipocytes of 6.97 cm³ an elevation of 8%, 25%, and 58%, respectively. Furthermore, the HGLI diet increased liver and pancreatic fat deposition, altered and inflamed the intestinal epithelia, and increased TNF-α gene expression ( P =0.014) with a positive immunostaining in visceral adipose tissue and high plasma TNF-α in comparison with standard diet. The results suggest that this diet was able to generate changes commonly caused to solid diets with high fat or fructose-rich beverages. To the best of our knowledge, this is the first report in the literature concerning the properties of low-cost, sucrose-rich pellet-diet presenting high glycemic index and high glycemic load efficient on the development of obesity complications in Wistar rats that were subjected to diet-induced obesity. Therefore, the HGLI pellet-diet may be considered an effective tool to be used by the scientific community in experimental research.